Sports tourism in the gulf of tomini region - Mirdayani Pauweni; Tandiyo Rahayu; Mashuri Eko Winarno; Heny Setyawati; Aisah R Pomatahu (Universitas Riau, 2023)
(English) The Gulf of Tomini consists of areas in three provinces, namely North Sulawesi, Central Sulawesi, and Gorontalo. Gorontalo region which directly borders The Gulf of Tomini, consists of: Pohuwato, Boalemo, Gorontalo, Bone Bolango, and Gorontalo City. These regions have resources that have been utilized for the development of the tourism sector, thus becoming a destination for foreign and domestic tourists. The developed destinations include sports tourism destinations. This research aims to assess sports tourism activities in the Gulf of Tomini Region, and provide recommendations for the right time to visit the destination. This descriptive qualitative research used literature study and Focus Group Discussion methods to collect data. The main finding of this research is the recommendation of the right time for sports tourism in The Gulf of Tomini Region. Based on these findings, it can be recommended that natural sports tourism in The Gulf of Tomini Region should be carried out during the period December January February, and June July August, marine sports tourism in shallow waters in September October November and in deep waters from October to April.(Indonesian)Kawasan Teluk Tomini merupakan wilayah-wilayah yang terdiri dari tiga provinsi, yakni Sulawesi Utara, Sulawesi Tengah, dan Gorontalo. Wilayah Gorontalo yang berbatasan langsung dengan Teluk Tomini, terdiri dari: Kabupaten Pohuwato, Boalemo, Gorontalo, Bone Bolango, dan Kota Gorontalo. Wilayah-wilayah ini memiliki sumber daya yang telah dimanfaatkan untuk pengembangan sektor pariwisata, sehingga menjadi destinasi bagi wisatawan mancanegara dan domestik. Destinasi yang dikembangkan diantaranya adalah destinasi wisata olahraga. Penelitian ini bertujuan untuk mengkaji aktivitas wisata olahraga di Kawasan Teluk Tomini, dan memberikan rekomendasi waktu yang baik untuk berkunjung ke destinasi. Penelitian kualitatif deskriptif ini menerapkan metode kajian pustaka dan Focus Group Discussion untuk mengumpulkan data. Temuan utama penelitian ini adalah rekomendasi waktu yang baik untuk berwisata olahraga olahraga di Kawasan Teluk Tomini. Berdasarkan temuan tersebut, maka dapat direkomendasikan aktivitas wisata olahraga alam di Kawasan Teluk Tomini agar dilakukan selama periode Desember Januari Februari, dan Juni Juli Agustus, berwisata olahraga bahari di perairan dangkal pada September Oktober November, dan di perairan dalam pada Oktober hingga April. Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.